2015
DOI: 10.1049/iet-pel.2014.0623
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of digitally controlled LCL‐type grid‐connected inverter considering the delay effect

Abstract: Owing to LCL-filter resonance, a single loop may not be adequate to stabilise the digitally controlled LCL-type grid-connected inverter, thus the capacitor-current-feedback active damping is usually introduced. However, the computation and pulse-width modulation delays of the digitally controlled system significantly affect system stability and damping performance. Moreover, the delay varies when the duty-ratio update instant and sampling instant are changed. In this study, the Nyquist diagram is used to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
(99 reference statements)
2
27
0
Order By: Relevance
“…They also proposed a design method for a digital controller in the two stable regions. Similar conclusions were also drawn in [13,14]. However, these papers do not provide sufficient explanation of the inherent relationship between active damping and controller time delays.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…They also proposed a design method for a digital controller in the two stable regions. Similar conclusions were also drawn in [13,14]. However, these papers do not provide sufficient explanation of the inherent relationship between active damping and controller time delays.…”
Section: Introductionsupporting
confidence: 55%
“…Despite a vast amount of literature that has been published on the subject of LCL filter in grid-connected inverters, there is still no consensus on a stability evaluation method accounting for computation and pulse width modulation (PWM) delays [11][12][13][14][15][16][17]. Reference [11] presented pioneering research on active damping in discretetime domain taking time delays into account, and concluded that discrete-time active damping is not always stable, depending on the ratio of resonance frequency to sampling frequency.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, with one-sample delay (i.e., T d = T s ), the resonance still exists if a is between 1/6 and 1/2, as also analyzed in [26][27][28][29][30][31][32]34]. If (10) is fulfilled, the feedback AD in Fig.…”
Section: Digital Control Delay Impactmentioning
confidence: 81%
“…AD strategies based on feedback compensation are in essence the same while their differences mainly lie in the choice of states for feedback. Typical applications of proportional i C1 feedback can be found in [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. For 1 storder derivative feedback of u C1 , a high-pass filter (HPF) with a similar response is an alternative solution [35].…”
Section: Ad Subject To Different Options Of Single Statementioning
confidence: 99%
See 1 more Smart Citation